Dealumination Effect on ZSM-5 as a Bimetal Fe-Co Support for The Oxidative Desulfurization Process Catalyst - Adhani, Lisa; Susanto, Bambang Heru; Nasikin, Mohammad (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2024)
Petroleum fuel is still the main energy source today but causes environmental problems such as SOx gas emissions. The Oxidative Desulfurization (ODS) method removes sulfur from fuel under mild conditions. ZSM-5 is a catalyst framework considered promising in the ODS process but the small pores cause a steric barrier. The hydrophobic, mesoporous Fe-Co/ZSM-5Hierarchy catalyst was designed using the dealumination method with steam treatment to overcome the steric barrier and biphasic hindrances which are problems in this ODS process. The Fe-Co/ZSM-5Hierarchy catalyst is effective for the ODS process at a temperature of 45 °C, 45 min, the amount of catalyst used is 0.2 g, oxidant at an O/S ratio of 2, and without mass transfer agents. The embedded Fe-Co ratio shows effective mass activity by providing a TOF number of 205 h-1 on the Fe-Co(5)/ZSM-5 Hierarchy and 157 h-1 on the Fe-Co(15)/ZSM-5 Hierarchy catalyst.